P218 The epidemiological, healthcare and societal burden and costs of asthma in the UK and member nations: analyses of national databases. (12th November 2015) - Mukherjee, M; Stoddart, A; Gupta, R; Nwaru, B; Heaven, M; Farr, A; Fitzsimmons, D; Bandyopadhyay, A; Aftab, C; Simpson, C; Lyons, R; Fischbacher, C; et al.
Abstract : Background: Developing a comprehensive picture of the burden of asthma in the UK will enable informed national decisions about care provision and planning. We sought to provide the first UK-wide estimates of the epidemiology, healthcare utilisation and costs of asthma. Methods: We undertook analyses of national health surveys, routine healthcare and administrative datasets over the period 2010–12. Economic modelling was carried out to estimate costs. Estimates were calculated for each nation and the UK as a whole. Results: The UK lifetime prevalence of patient-reported symptoms suggestive of asthma in 2010–11 was 30.7% (95% Confidence Intervals [CI] 29.2–32.2; equivalent to [ ] 18, 949, 516 people), lifetime prevalence of patient-reported physician-diagnosed asthma was 15.9% (95% CI 14.7–17.1; 10, 841, 030 people), annual prevalence of patient-reported physician-diagnosed-and-treated asthma was 9.1% (95% CI 8.0–10.2; 5, 765, 237 people), annual prevalence of GP reported-and-diagnosed asthma was 8.2% (95% CI 8.2–8.2; 5, 215, 607 people) and annual prevalence of GP reported-and-diagnosed-and-treated asthma was 6.0% (95% CI 6.0–6.0; 3, 946, 796 people). In 2011–12, asthma resulted in an estimated: 6, 392, 670 primary-care consultations; 93, 916 inpatient-care episodes; 1, 864 (317 paediatric and 1, 547 adult) intensive-care unit episodes; 36, 800 disability living allowance (DLA) claims; and 1, 160 deaths. The estimated cost of asthma in the UK was at least £1.1billion in 2011–12: 75% of this was for primary-care (60% prescribing and 15% consultations), 13% for DLA claims, and 10% for hospital care. Conclusions: We found that asthma is very common, affecting at least 3.95 million people, and that it is responsible for substantial morbidity, healthcare and societal costs in the UK. Setting ambitious targets for improving asthma outcomes is paramount and resources should be targeted to improving community-based prescribing decisions and reducing the risk of asthma exacerbations and associated hospitalisations and deaths. Funding: Asthma UK, with additional support from the Edinburgh Health Services Research Unit and Farr Institute, UK.